2014
DOI: 10.1097/ss.0000000000000086
|View full text |Cite
|
Sign up to set email alerts
|

Coadaptation of Plants to Multiple Stresses in Acidic Soils

Abstract: Soil acidification is an increasing problem in agricultural production and ecological stability worldwide. An understanding of the mechanisms by which plants adapt to acidic soils would help address this problem. Poor plant growth in acidic soils results from a variety of factors, including proton toxicity; deficiencies in nitrogen, phosphorus, calcium, magnesium; and toxicities of various metals (aluminum (Al), manganese, iron). Aluminum toxicity is generally the primary limitation for plant growth in acidic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 97 publications
0
29
0
Order By: Relevance
“…Acid soils are characterized by poor nitrification and high levels of soluble Al, while neutral to calcareous soils show high nitrification and lower levels of Al toxicity ( Zhao et al, 2014 ; Che et al, 2015 ). The two main inorganic N sources available for plant growth are NH 4 + and NO 3 - .…”
Section: Link Between Plant Al Tolerance and Inorganic N Preferencementioning
confidence: 99%
See 4 more Smart Citations
“…Acid soils are characterized by poor nitrification and high levels of soluble Al, while neutral to calcareous soils show high nitrification and lower levels of Al toxicity ( Zhao et al, 2014 ; Che et al, 2015 ). The two main inorganic N sources available for plant growth are NH 4 + and NO 3 - .…”
Section: Link Between Plant Al Tolerance and Inorganic N Preferencementioning
confidence: 99%
“…Since low pH increases the concentrations of soluble Al in soils, the alkalization of the rhizosphere was proposed to be an important mechanism of plant Al tolerance ( Matsumoto, 2000 ; Kochian et al, 2004 ; Ma, 2007 ). However, several studies demonstrated that H + could alleviate Al toxicity because H + competed with Al 3+ for adsorption to the root surface ( Kinraide et al, 1992 ; Godbold et al, 1995 ; Zhao et al, 2009 ; Zhao et al, 2014 ). A supply of H + also alleviated Al toxicity in bacteria ( Kinraide and Sweeney, 2003 ) and yeast ( Zhao et al, 2017 ).…”
Section: Effects Of Nh 4 + No mentioning
confidence: 99%
See 3 more Smart Citations